Right of the detainee to have contact with a lawyer or solicitor and to direct consultation with them as an element of the Right of Defence - Żylińska, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The subject of this study is an analysis of the detainee’s right to have contact with a lawyer or solicitor and to direct consultation with them as an element of the right of defence. The right of defence is also applicable with respect to detainees. An important element in the process of its fulﬁ lment is the real contact of the detainee with a lawyer or solicitor. In particular, it allows the detainee to obtain legal advice, not only with respect to the current procedural situation but also with respect to further legal consequences and ultimately eﬀect the rights of defence to which the detainee is eligible in the manner consistent with his/her actual procedural interests. The author’s intention is to examine the scope and rules of application of the rights of the detainee as set out in Art. 245 of the Criminal Procedure Code and the analysis of its eﬀect on the detainee’s eﬀective exercising of the right of defence.
Keywords: prawa zatrzymanego; kontakt z prawnikiem lub radcą prawnym; prawo do obrony